Protean career of professionals at E&E industry: the moderating role of career strategies - Wong, Siew Chin; Mohd Rasdi, Roziah (2014)
The purpose of this paper is to examine the influence of individual-related factors and the moderating role of career strategies on protean career among professional employees in Malaysian Electrical and Electrics (E&E) industry. This study draws on a sample of 306 professional employees in 18 Electrical and Electronics MNCs in Malaysia. Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed for data analysis purposes. Our results suggest that individual-related variables are potential predictors of protean career. There is significant moderating effect of career strategies on the relationship between goal orientation and protean career among professional employees in E&E industry. Practical interventions for HRD professionals were suggested to assist individuals and organisations towards protean career in the career management process.